Effective Use of Parenting Coordination: Considerations for Legal and Mental Health Professionals. (27th July 2020) - Sullivan, Matthew; Burns, Annette
Abstract : Parenting Coordination (PC) is a dispute resolution and case management role to assist high conflict coparents (Coates et al., Family Court Review, 2004; 42, 246–262; Sullivan, Journal of Child Custody, 2008; 5, 3–24; Carter & Lally, Parenting Coordination in Post‐Separation Disputes, 2014; Fidler, Canadian Family Law Quarterly, 2012; 31, 237–273). A revision of the original practice 2005 guidelines for parenting coordination was just published by the Association of Families and Conciliation Courts in 2019, providing an update for the family justice community about developments in the parenting coordinator (PC) role in the last 14 years. This article focuses on how family law professionals can support effective parenting coordination practice in their jurisdiction. Support begins with understanding the PC role as the most intensive intervention available at this time for high conflict coparents, and guidance about what types of cases are appropriate for referral and which are not. A description of the essential components of appointment orders, parenting coordination procedures, and court review are provided as well to best structure the parenting coordination process for success. Finally, the article addresses how jurisdictions can support the development and maintenance of this unique role. Key Points for the Family Court Community: Parenting Coordination is the most intensive intervention for coparents who have intractable conflict as they implement shared parenting. The article describes the essential functions of the Parenting Coordination role to assist family law professionals to make appropriate appointments in their jurisdiction. Several procedural structures are presented that should be considered when appointing a Parenting Coordinator. Recommendations are provided that the Court, the bar and mental health experts to support the development of Parenting Coordination in their jurisdiction.